Urinary Isoxanthohumol Is a Specific and Accurate Biomarker of Beer Consumption. Issue 4 (29th January 2014) - Quifer-Rada, Paola; Martínez-Huélamo, Miriam; Chiva-Blanch, Gemma; Jáuregui, Olga; Estruch, Ramon; Lamuela-Raventós, Rosa M.
Abstract: Biomarkers of food consumption are a powerful tool to obtain more objective measurements of dietary exposure and to monitor compliance in clinical trials. In this study, we evaluated the effectiveness of urinary isoxanthohumol (IX) excretion as an accurate biomarker of beer consumption. A dose-response clinical trial, a randomized, crossover clinical trial, and a cohort study were performed. In the dose-response trial, 41 young volunteers (males and females, aged 28 ± 3 y) consumed different doses of beer at night and a spot urine sample was collected the following morning. In the clinical trial, 33 males with high cardiovascular risk (aged 61 ± 7 y) randomly were administered 30 g of ethanol/d as gin or beer, or an equivalent amount of polyphenols as nonalcoholic beer for 4 wk. Additionally, a subsample of 46 volunteers from the PREDIMED (Prevenciόn con Dieta Mediterránea) study (males and females, aged 63 ± 5 y) was also evaluated. Prenylflavonoids were quantified in urine samples by liquid chromatography coupled to mass spectrometry. IX urinary recovery increased linearly with the size of the beer dose in male volunteers. A significant increase in IX excretion (4.0 ± 1.6 μ g/g creatinine) was found after consumption of beer and nonalcoholic beer for 4 wk ( P < 0.001). Receiver operating characteristic curves showed that IX is able to discriminate between beer consumers and abstainers with a sensitivity of 67% and specificity of 100% (positive predictive value = 70%, negative predictive value = 100% in real-life conditions). IX in urine samples was found to be a specific and accurate biomarker of beer consumption and may be a powerful tool in epidemiologic studies. This trial was registered at the International Standard Randomized Controlled Trial registry as ISRCTN72996101 (study 1), ISRCTN95345245 (study 2), and ISRCTN35739639 (study 3).